2021
DOI: 10.1007/s00394-021-02639-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long-term moderate exercise and Western-type diet on oxidative/nitrosative stress, serum lipids and cytokines in female Sprague Dawley rats

Abstract: Purpose Regular exercise reduces obesity and the risk of cardiovascular disease. However, health-promoting benefits of physical activity are commonly associated with increased inflammation and oxidative stress. Here, we tested whether constant moderate exercise is able to prevent or attenuate the oxidative/nitrosative stress, inflammation, and serum lipids in lean and obese rats. Methods Four-month-old female Sprague Dawley rats received standard or a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
4
6
0
Order By: Relevance
“…Moreover, in agreement with us, unchanged TNF-α levels were found by Bedoui and colleagues in male rats fed for 10 weeks with a high-fat diet ( 71 ), and by Semeraro and colleagues in female rats fed for 10 months with a high-fat diet ( 72 ). These changes suggest additional damage to intestinal cell function and structure.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, in agreement with us, unchanged TNF-α levels were found by Bedoui and colleagues in male rats fed for 10 weeks with a high-fat diet ( 71 ), and by Semeraro and colleagues in female rats fed for 10 months with a high-fat diet ( 72 ). These changes suggest additional damage to intestinal cell function and structure.…”
Section: Discussionsupporting
confidence: 88%
“…[24][25][26] Extensive studies have demonstrated that exercise protects against cardiovascular dysfunction produced by obesity/HFD including improvement of baroreflex sensitivity, a reduction of sympathetic activity and attenuations of BP and HR through modifications of prohypertensive RAS and inflammatory responses. [7][8][9][10]14,15,17,19,35 Consistent with this, we found that 10 weeks of exercise reduced cardiac sympathetic activity and increased cardiac vagal activity and spontaneous baroreflex sensitivity leading to decreases in heart rate, decreased plasma levels of ANG II and leptin and attenuated pressor responses to centrally administered ANG II and leptin. These functional changes were accompanied by reduction of upregulated expression of most prohypertensive genes and a marker of BBB permeability in the PVN in HFD-fed offspring of both normotensive and hypertensive dams.…”
Section: Discussionsupporting
confidence: 87%
“…[7][8][9] The underlying mechanisms have been associated with the inhibition of the renin-angiotensin system (RAS) and inflammation in the heart and adipose tissue and in brain regions involved in cardiometabolic regulation including the hypothalamic paraventricular nucleus (PVN). [10][11][12][13][14][15][16][17] There are few recent studies exploring the effect of exercise on the adverse effects in offspring produced by prenatal challenges. [18][19][20] In the male offspring of mothers fed a HFD during gestation and lactation, a short period of early postweaning exercise had lasting beneficial effects on body weight, visceral fat, and hormonal profile such as leptin, insulin, and triglyceride.…”
mentioning
confidence: 99%
“…Mechanism by which moderate physical activity reduced increased levels of gastric ADMA via its antioxidant, anti-inflammation, and anti-apoptotic properties (Semeraro et al, 2022). In addition to increase HSP70 (Nakhjavani et al, 2012) as shown in our results.…”
Section: Discussionsupporting
confidence: 74%